Fundamental understanding of the setting behaviour of the alkali activated binders based on ground granulated blast furnace slag and fly ash. (12th July 2021) - Nedunuri, Aparna Sai Surya Sree; Muhammad, Salman
Highlights: Proportion of fly ash in the GGBFS-fly ash mixture governs the setting time of AASF. The mechanical evolution of network in AASF mixtures was studied by storage modulus. The rate of coagulation and rigidification is higher in AASF when compared with OPC. Quick setting of AASF mixtures is due to rapid formation of hydration products. Abstract: This study aims to investigate the setting of alkali activated ground granulated blast furnace slag and fly ash mixtures by following the mechanical and chemical evolution of structure of the precursor-activator suspension during early ages. The mechanical evolution was followed by measuring the evolution of storage modulus. The chemical evolution was followed by measuring the amount of hydrates formed at different times. The dependence of setting time of alkali activated slag mixtures on the amount of incorporated fly ash, molar modulus and activator dosage was also studied. This study shows that the quick setting of alkali activated slag mixtures is due to rapid coagulation followed by rapid rigidification of network with the formation of hydration products. In comparison, the setting in OPC systems is due to a network formed by partially hydrated or anhydrous cement particles. The proportion of fly ash in GGBFS-fly ash mixture and molar modulus of the activator were found to have a significant effect on the setting time of alkali activated ground granulated blast furnace slag and fly ash binders.